Composition analysis of Ta3N5/W18O49 nanocomposite through XPS - Daniel Jones (Surface Science Spectra, 2018)
A characterization of a nanocomposite material consisting of Ta3N5 nanoparticles and W18O49 nanowires is presented. The material is of interest for photocatalytic applications, with a focus on pollution reduction through the photodegradation of dye waste; under white light illumination, the combination of Ta3N5 and W18O49 yielded an enhanced rate of dye degradation relative to Ta3N5 particles alone. The facile method of synthesis is thought to be a promising route for both upscale and commercial utilization of the material. X-ray photoelectron spectroscopy revealed a core–shell composite structure with W18O49 present as an overlayer on Ta3N5; the analyzed spectra for the C 1s, O 1s, Ta 4f, N 1s, W 4f, and Na 1s regions are reported. It should be noted that due to differential charging of the underlying Ta3N5 component relative to the W18O49 shell, an additional uncompensated voltage shift may exist in the Ta 4f and N 1s spectra.